The Royal Court's Role in Patronizing Thai Textiles - Boonpratsaphai, Wanchanok; Rohitasuk, Sitthidham; Nop-udomphan, Kittikorn (Journal of Posthumanism, 2025)
This research explores the Thai royal court’s role in supporting traditional Thai textiles, tracing their evolution from folk art to a blend of traditional and modern aesthetics that has gained global recognition. The researcher gathered data from primary sources such as royal records and historical journals, social media interviews, and secondary sources like magazine articles and interviews with relevant informants. The information was analyzed using historical methods and presented descriptively. Findings show that royal patronage began with Her Majesty Queen Sirikit, the Queen Mother, who, during a six-month diplomatic tour to the U.S. and Europe, realized Thailand lacked a national costume. This led to the creation of eight official Thai national costumes, which have since become iconic and are still in use today.